2017
DOI: 10.1177/2050313x17745211
|View full text |Cite
|
Sign up to set email alerts
|

Rapid resolution of left ventricular thrombus with apixaban therapy

Abstract: It is a common medical practice to anticoagulate an asymptomatic left ventricular mural thrombus following an ST-elevation myocardial infarction using a vitamin K antagonist. Novel oral anticoagulants have not been studied extensively in this context, and therefore, no recommendations have been made for their use. A 67-year-old male physician with no significant medical history presented to the cardiology clinic complaining of shortness of breath that had been gradually worsening over a 2-week period and was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…There have also been several case reports describing the effectiveness of DOACs in the treatment of left ventricular (LV) thrombus. 9 , 10 However, the literature describing the use of DOACs to treat right-sided thrombus is sparse and large-scale randomized control trials (RCT) are lacking in this area. Even the current recommendations to use oral vitamin K antagonists for left-sided intracardiac clots are largely based on observational studies and not RCTs, as RCTs would be rather difficult to conduct in this cohort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have also been several case reports describing the effectiveness of DOACs in the treatment of left ventricular (LV) thrombus. 9 , 10 However, the literature describing the use of DOACs to treat right-sided thrombus is sparse and large-scale randomized control trials (RCT) are lacking in this area. Even the current recommendations to use oral vitamin K antagonists for left-sided intracardiac clots are largely based on observational studies and not RCTs, as RCTs would be rather difficult to conduct in this cohort.…”
Section: Discussionmentioning
confidence: 99%
“…There were no clear guidelines on how to manage this unique situation and the patient preferred an oral anticoagulant that did not require frequent monitoring. Due to the efficacy and safety profile of apixaban, 17 and its success in treating intracardiac thrombus, 9 , 10 we decided to treat our patient with apixaban. After discussing the potential risks and benefits, the patient was started on apixaban 10 mg twice daily initially for 7 days and then 5 mg a day thereafter.…”
Section: Discussionmentioning
confidence: 99%
“…Rivaroxaban was also used for treating a case of intraventricular thrombus in Chagas disease (13) and dilated cardiomyopathy (14). Several reported cases have shown the efficacy of apixaban in cases of intraventricular thrombi without increased risk of thromboembolic or bleeding issues even when used with DAPT in patients with post-MI (15, 16).…”
Section: Discussionmentioning
confidence: 99%
“…Nieman et al reported that anticoagulation with warfarin therapy can resolve fresh thrombi, but not chronic ventricular thrombi after MI (Niemann et al, 2012 ). However, several case reports have shown the feasibility of NOAC treatment of LV thrombi with dabigatran (Kaku, 2013 ; Nagamoto et al, 2014 ; Chung et al, 2015 ; Kolekar et al, 2015 ; Ohashi et al, 2015 ) or factor Xa inhibitors (Nakasuka et al, 2014 ; Padilla Pérez et al, 2014 ; Kaya et al, 2016 ; Makrides, 2016 ; Mano et al, 2016 ; Berry et al, 2017 ; Seecheran et al, 2017 ; Smetana et al, 2017 ). In the cases describing dabigatran to resolve LV thrombi, the doses varied between 110 and 150 mg bid and the resolution of the thrombi was confirmed after 3 weeks to 4 months (Hori et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…We chose dabigatran due to the high bleeding risk of our patient and the availability of an efficient antidote (idarucizumab), which had shown rapid and complete reversion of the anticoagulant activity of dabigatran in the RE-VERSE AD study (Pollack et al, 2015 ). Only few cases have been reported in the literature where triple therapy was used to resolve a LV thrombus with Factor Xa inhibitors (Makrides, 2016 ; Mano et al, 2016 ; Berry et al, 2017 ; Seecheran et al, 2017 ; Smetana et al, 2017 ) or dabigatran (Chung et al, 2015 ; Ohashi et al, 2015 ). In contrast to these described cases, apparent development of a LV thrombus under dabigatran treatment has been published recently (Adar et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%